2019
DOI: 10.3390/sym11050636
|View full text |Cite
|
Sign up to set email alerts
|

Nambu-Jona Lasinio and Nonlinear Sigma Models in Condensed Matter Systems

Abstract: We review various connections between condensed matter systems with the Nambu-Jona Lasinio model and nonlinear sigma models. The field theoretical description of interacting systems offers a systematic framework to describe the dynamical generation of condensates. Resent findings of a duality between the Nambu-Jona Lasinio model and the nonlinear sigma model enables us to investigate various properties underlying both theories. In this review we mainly focus on inhomogeneous condensations in static situations.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…This feature has been investigated in the (1+1) dimensional Nambu-Jona-Lasinio model or the chiral Gross-Neveu model [41][42][43][44][45]. Recently, the connection between the Nambu-Jona-Lasinio model and the non-linear sigma model is also of particular interest to the inhomogeneous condensate [46]. Moreover, the generalized Ginzburg-Landau approach with higher derivatives of the order parameter has been developed and it has been revealed that the LOFF phase of the chiral condensate is energetically preferred in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…This feature has been investigated in the (1+1) dimensional Nambu-Jona-Lasinio model or the chiral Gross-Neveu model [41][42][43][44][45]. Recently, the connection between the Nambu-Jona-Lasinio model and the non-linear sigma model is also of particular interest to the inhomogeneous condensate [46]. Moreover, the generalized Ginzburg-Landau approach with higher derivatives of the order parameter has been developed and it has been revealed that the LOFF phase of the chiral condensate is energetically preferred in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Such similarities can be explained by several physical setups, in which the two-dimensional CP N −1 sigma model effectively describes various physical properties of four-dimensional gauge theories; non-Abelian vortices in the non-Abelian gauge-Higgs models [5-10, 10, 11] and dense QCD [12][13][14][15], long strings in Yang-Mills theories [16], and an appropriately compactified Yang-Mills theory [17]. Non-perturbative properties of the CP N −1 model have long been studied analytically by the gap equations with the large-N approximation [2][3][4][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and by lattice simulations [36][37][38][39][40][41][42][43][44][45][46][47][48][49]. In the previous work [47,48] of the present authors, they have studied the CP N −1 model on S 1 s (large) × S 1 τ (small) by lattice Monte Carlo simulations.…”
Section: Introductionmentioning
confidence: 99%
“…This feature has been investigated in the (1+1) dimensional Nambu-Jona-Lasinio model or the chiral Gross-Neveu model [41][42][43][44][45]. Recently, the connection between the Nambu-Jona-Lasinio model and the non-linear sigma model is also of particular interest to the inhomogeneous condensate [46]. Moreover, the generalized Ginzburg-Landau approach with higher derivatives of the order parameter has been developed and it has been revealed that the LOFF phase of the chiral condensate is energetically preferred in ref.…”
Section: Introductionmentioning
confidence: 99%